1963
DOI: 10.1002/bip.360010409
|View full text |Cite
|
Sign up to set email alerts
|

Conformational aspects of polypeptides. XI. The nitroaromatic effect

Abstract: On p. 378. Fig. 6, the lower left axis shonld read Residue Rotation, [R'] ; the right axis On p. 394, procedure 6, line 6 should read m.p. (corr.) 194-195°C.; [a]'," = + 12.75' should read Molar Ellipticity, 0.(c = 1.17, glacial aretic acid). Some Optical Properties of Poly-1-benzyl-L-histidine snd Poly-L-histidineHiopolymers, 1, 277-294 (1sCi3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In this connection, a few publications have recently reported very stimulating results on the preferred helical handedness of homo‐oligopeptides based on C α ‐ tetra substituted α‐amino acids with only side‐chain chirality 63–66. As far as the large field of helical oligo‐ and polypeptides formed by C α ‐ tri substituted α‐amino acids is concerned, only a limited number of scattered data is available,3–5, 7–10, 67–78 which does not allow one to extract a general picture of this important 3D‐structural issue.…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, a few publications have recently reported very stimulating results on the preferred helical handedness of homo‐oligopeptides based on C α ‐ tetra substituted α‐amino acids with only side‐chain chirality 63–66. As far as the large field of helical oligo‐ and polypeptides formed by C α ‐ tri substituted α‐amino acids is concerned, only a limited number of scattered data is available,3–5, 7–10, 67–78 which does not allow one to extract a general picture of this important 3D‐structural issue.…”
Section: Resultsmentioning
confidence: 99%
“…PClBLA studied in this work also follows this pattern 42, 43. The helix‐sense inversion of copolymers studied by Goodman and his group1, 2, 6–8, 16, 17 in earlier years seems to involve the same transition mechanism 44…”
Section: Discussionmentioning
confidence: 82%
“…Poly(β‐benzyl L ‐aspartate) (PBLA) takes the left form and does not exhibit any screw‐sense inversion. Reversal of the helix sense in copolymer systems such as those comprising X 1 = nitrobenzyl and X 2 = benzyl residues has been extensively investigated by Goodman and his coworkers1, 2 as early as in 1960s. An extensive investigation by Hashimoto et al3–5 revealed that the screw‐sense reversal takes place sensitively with the chemical nature of the surrounding media.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that polyaspartates form right‐ or left‐handed helices depending on the side chain structure, solvent, and temperature . While poly(β‐benzyl‐L‐aspartate) (PBLA) forms a left‐handed α‐helix (αL‐helix) in chloroform, polyaspartates bearing para ‐substituted benzyl groups, long n ‐alkyl groups, phenethyl moieties, etc, form a right‐handed α‐helices (αR‐helices) .…”
Section: Introductionmentioning
confidence: 99%